2015
DOI: 10.1016/j.anifeedsci.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses in mullet Mugil liza juveniles fed with guar gum supplemented diets

Abstract: a b s t r a c tThis study aimed to evaluate the effects of adding guar gum, a non-starch polysaccharide, to the diet of Mugil liza juveniles. The juveniles (mean weight = 0.38 ± 0.01 g) were fed one of three diets with increasing supplement levels (4%, 8%, and 12%) and a control diet without additional gum for 60 days, in order to evaluate the effects on zootechnical performance, proximate composition, liver parameters, morphological alterations to the intestinal tract, and modulation of gastrointestinal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…The mullets in the present study exhibited distribution of bacteria along the gastrointestinal tract similar to previous works (Ramos et al 2015a(Ramos et al , 2015b. Bacteria were more abundant in the stomach than in intestinal sections; the authors identify that this microbial pattern could indicate that M. liza utilizes the bacterial biomass for its own growth, similar to ruminant animals, whose nutrition relies mainly on bacterial-fermentable products and the microbial biomass present in the forestomach (Hill et al 2008).…”
supporting
confidence: 71%
“…The mullets in the present study exhibited distribution of bacteria along the gastrointestinal tract similar to previous works (Ramos et al 2015a(Ramos et al , 2015b. Bacteria were more abundant in the stomach than in intestinal sections; the authors identify that this microbial pattern could indicate that M. liza utilizes the bacterial biomass for its own growth, similar to ruminant animals, whose nutrition relies mainly on bacterial-fermentable products and the microbial biomass present in the forestomach (Hill et al 2008).…”
supporting
confidence: 71%
“…A limited number of studies show that modifying the diet of the fish can result in alterations of the gut microbiota, but this is not always the case. Diets containing guar gum, (non-starch polysaccharide) fed to the omnivorous mullet, Mugil liza (100) or soy proteins to the carnivorous rainbow trout (101) induce alterations in the bacterial quantity and composition in the GIT. In zebrafish, administration of dietary nucleotides results in modifications of the microbiota and reduction in fatty acid oxidation in muscle and liver as well as lower inflammatory tone (102).…”
Section: Factors Affecting Fish Gut Microbiotamentioning
confidence: 99%
“…Similar results have been reported in several fishes, that is, Enes et al (2013) reported that plasma cholesterol did not decrease in white sea bream, Diplodus sargus by GG supplementations at 4-12% to diet. In addition, liver cholesterol increased by feeding 12% GG-supplemented diet in mullet (L. R. V. Ramos et al, 2015). In aquatic animals, dietary cholesterol is absorbed by the stomach and intestine, and it is influenced by several factors such as dietary fat composition, bile acid secretion, and activity of cellular transporters in digestive tracts (Lammert & Wang, 2005).…”
Section: Discussionmentioning
confidence: 99%